2009
DOI: 10.4049/jimmunol.0900339
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD40 Monoclonal Antibody Synergizes with CTLA4-Ig in Promoting Long-Term Graft Survival in Murine Models of Transplantation

Abstract: Blockade of the CD40/CD154 signaling pathway using anti-CD154 Abs has shown promise in attenuating the alloimmune response and promoting long-term graft survival in murine model systems, although side effects observed in humans have hampered its progression through clinical trials. Appropriately designed anti-CD40 Abs may provide a suitable alternative. We investigated two isoforms of a novel monoclonal rat anti-mouse CD40 Ab (7E1) for characteristics and effects mirroring those of anti-CD154: 7E1-G1 (an IgG1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 73 publications
1
69
0
1
Order By: Relevance
“…Nevertheless, mouse skin allograft is a predictive preclinical model frequently used in the early phase of development of new immunosuppressive drugs in transplantation (42)(43)(44). The skin graft survival obtained in our study is remarkable because, without bone marrow transplantation, not many treatment protocols could result in similar graft outcomes, especially when fully allogeneic BALB/c and C57BL/6 mice are used for donors and recipients (43,44).…”
Section: Il13mentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, mouse skin allograft is a predictive preclinical model frequently used in the early phase of development of new immunosuppressive drugs in transplantation (42)(43)(44). The skin graft survival obtained in our study is remarkable because, without bone marrow transplantation, not many treatment protocols could result in similar graft outcomes, especially when fully allogeneic BALB/c and C57BL/6 mice are used for donors and recipients (43,44).…”
Section: Il13mentioning
confidence: 69%
“…The skin graft survival obtained in our study is remarkable because, without bone marrow transplantation, not many treatment protocols could result in similar graft outcomes, especially when fully allogeneic BALB/c and C57BL/6 mice are used for donors and recipients (43,44). Therefore, our results suggest that IL-7R blockade may present as a promising therapeutic candidate in organ transplantation.…”
Section: Il13mentioning
confidence: 72%
“…Therefore, we can conclude that 33D1 has no deleting properties when used in vivo. A novel rIgG2b Ab against mouse CD40 (29), which is expressed on cDCs, was also not able to induce deletion in a recent report supporting the notion that cDCs can be resistant to Ab-mediated deletion. To verify that conjugating peptide to the Ab did not alter its binding specificity we performed a competitive binding assay in which we first incubated splenocytes with the conjugated 33D1 Ab and then second with 33D1-PE.…”
Section: Cd4mentioning
confidence: 70%
“…et al, 2001). Gilson et al (2009) found that the IgG2b, but not the IgG1 antibody had a synergistic effect o n g r a f t s u r v i v a l w h e n c o m b i n e d w i t h C T L A -4-Ig, and hypothesized that the use of alternative antibody isotypes may encourage the development of new reagents that are as effective as anti-CD154 antibodies, but without harmful clinical effects.…”
Section: Interfering With Cd40/cd154 Ligationmentioning
confidence: 99%
“…These studies show further that CD154's concentration is increased in hypertensive patients included non-diabetic and pre-diabetic persons with metabolic syndrome (Unek et al, 2010). In an effort to overcome these complications, Gilson et al (2009) compared two different isotypes of anti-CD40 monoclonal antibodies. Isotypes are any one of the five main structurally and functionally distinct categories of antibodies (Janeway C.A.…”
Section: Interfering With Cd40/cd154 Ligationmentioning
confidence: 99%